TP53 Mutation Spectrum in Smokers and Never Smoking Lung Cancer Patients - Halvorsen, Ann R.; Silwal-Pandit, Laxmi; Meza-Zepeda, Leonardo A.; Vodak, Daniel; Vu, Phuong; Sagerup, Camilla; Hovig, Eivind; Myklebost, Ola; Børresen-Dale, Anne-Lise; Brustugun, Odd T.; Helland, Åslaug (Frontiers in Genetics, 2016)
Abstract Background: TP53 mutations are among the most common mutations found in lung cancers, identified as an independent prognostic factor in many types of cancers. The purpose of this study was to investigate the frequency and prognostic impact of TP53 mutations in never-smokers and in different histological subtypes of lung cancer. Methods: We analysed tumour tissue from 394 non-small cell carcinomas including adenocarcinomas (n=229), squamous cell carcinomas (n=112), large cell carcinomas (n=30) and others (n=23) for mutations in TP53 by the use of Sanger sequencing (n=394) and next generation sequencing (n=100). Results: TP53 mutations were identified in 47.2% of the samples, with the highest frequency (65%) of mutations among squamous cell carcinomas. Among never-smokers, 36% carried a TP53 mutation, identified as a significant independent negative prognostic factor in this subgroup. For large cell carcinomas, a significantly prolonged progression free survival was found for those carrying a TP53 mutation. In addition, the frequency of frameshift mutations was doubled in squamous cell carcinomas (20.3%) compared to adenocarcinomas (9.1%). Conclusion: TP53 mutation patterns differ between the histological subgroups of lung cancers, as also influenced by smoking history. This indicates that the histological subtypes in lung cancer are genetically different, and that smoking-induced TP53 mutations may have a different biological impact than TP53 mutations occurring in never-smokers.